Copyright in Fire Insurance Plans - Dryden, Jean (Archivaria)

(untitled) (Association of Canadian Archivists, 2021)
Fire insurance plans are among the most valuable records documenting the development of Canada’s cities and towns during the late 19th and 20th centuries. Many of these plans are preserved in Canada’s archives and libraries. However, for nearly three decades, making copies for researchers and (more recently) digitizing for online access have been subject to a copyright “chill” as a result of the copyright claims of the companies that created these plans and their successors. This article recounts the history of Canadian fire insurance plans preserved in Canadian repositories and establishes their current copyright status in terms of ownership and duration. The article then explores the extent to which the copyright concerns are justified and offers possible solutions.